Experiencing Professional Doubts: A Narrative Study of Islamic Religious Education Teacher Candidates - Erniati, Erniati; Mania, Sitti; Kasmah, Kasmah; Saputra, Muh. Aril Widi (Institut Agama Islam Negeri Imam Bonjol Padang, 2026)
This study aims to explore how prospective Islamic Religious Education teachers experience and interpret professional doubts during their transition from university coursework to real classroom practice. The research focuses on understanding the feelings, meanings, and identity negotiations that emerge as students confront the realities of teaching. A qualitative narrative inquiry design was employed, involving four final semester students from a public university in Indonesia. Data were collected through a series of in-depth interviews and reflective dialogues, then analysed thematically to identify recurring patterns and significant meanings within participants’ narratives. The findings reveal four dominant themes: the perceived dual responsibility of transferring knowledge and moral values, lack of confidence in public communication, emotional unpreparedness in managing classroom dynamics, and discomfort with crowded social environments. These doubts are shaped by the interaction between personal characteristics and structural expectations of the teaching profession. Rather than functioning solely as obstacles, doubts serve as reflective turning points that encourage deeper self-awareness, value clarification, and adaptive coping strategies. The study concludes that professional doubt is an integral part of teacher identity formation. Teacher education programs should therefore provide reflective spaces and emotional support to help students transform doubt into professional resilience and sustained commitment.